Effect of Different Filler Materials in the Development of Bipolar Plate Composite for Polymer Electrolyte Membrane Fuel Cell (PEMFC) - Ahmad, Mohd Shakir; Selamat, Mohd Zulkefli; Mohd Daud, Mohd Ahadlin; Mohamad Yunus, Indera Kasuma; Azman, Mohd Syafiq (Trans Tech Publications, Switzerland, 2013)
Abstract. In Polymer Electrolyte Membrane Fuel Cell (PEMFC), bipolar plate is considered one of the most important components. Bipolar plate has a multi-functional in the fuel cell stack. The materials used in producing bipolar plate are greatly affecting its final properties. Through this study, the properties of bipolar plate composite will be observed. The based composition of this composite is 80% for multi-filler material and 20% binder material. Polypropylene (PP) will be used as binder material and for filler materials, Graphite (Gr) is the main filler and for the second filler materials its will vary with the usage of Carbon Black (CB), Iron (Fe), and Aluminum (Al) powder. The formation of this composite is produced through compression molding. The effect of different filler material loading on the properties such as electrical conductivity, bulk density and shore hardness are observed. The result showed the increasing of electrical conductivity as the increased the CB and Fe loading. But for Al, the result showed the decreasing of electrical conductivity as the loading of Al has been increased. Meanwhile the usage of CB clearly shown an improvement in electrical conductivity and able to meet the DOE target properties for development of PEMFC bipolar plate.